Consular Protection in Crisis: Vietnam’s Response During the COVID-19 Pandemic - Hanh Thi Nguyen; Linh Hoang Vo (Journal of Liberty and International Affairs, 2025)
Consular protection was a distinctive mission through which states fulfilled their fundamental responsibilities and provided essential services to their citizens beyond their borders. Consular missions were called upon to carry out protection activities when citizens overseas faced crises. The COVID-19 pandemic posed enormous challenges to governments in delivering such services. With a large number of citizens living, working, and travelling abroad, Vietnam was no exception. Despite its limited resources, Vietnam managed to respond effectively, offering an instructive case study of a middle-income country’s experience in applying Tindall and ’t Hart’s general analytical framework for consular protection during emergency situations. This case study underscored the need to develop a framework that accounts for the limited capacities of developing countries, as well as the unique challenges posed by the global nature of such crises.